The influence of natural rubber/Au nanoparticle membranes on the physiology of Leishmania brasiliensis - Barboza-Filho, Carlos G. [UNESP]; Cabrera, Flavio C. [UNESP]; Dos Santos, Renivaldo J. [UNESP]; De Saja Saez, Jose Antonio; Job, Aldo Eloizo [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
The development of nanotechnology has generated new means of disease diagnosis and treatment. Infectious diseases, including leishmaniasis, malaria, etc., have benefited from the advent of new nanomaterials and/or nanodevices capable of detecting specific antigens and antibodies with high specificity and low cost. In this paper, we present an investigation on a single-celled protozoan Leishmaniasis parasite, a disease considered of standard infectivity, given the high degree of immunological specificity. Natural rubber (NR) membranes incorporating gold nanoparticles (GNPs) were placed in the culture medium and the physiological behavior of Leishmania brasiliensis promastigotes was evaluated. The natural rubber membranes containing GNPs decreased the population growth rate, showing a lower index of living promastigotes (attached to the membrane surface) depending on the amount of nanoparticles deposited in the membrane surface. Such membranes may be used to develop a flexible band-aid for skin lesions from degenerative infection state, inhibiting the population growth of parasites in the lesions. In addition, natural rubber membranes would also stimulate angiogenesis in damaged tissues. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Gold nanoparticles; Natural rubber; Leishmania brasiliensis